PLAN PLESZEWA Z XIX WIEKU – WIZUALIZACJA TEMATYCZNA - Lorek, Dariusz (Badania Fizjograficzne Seria A - Geografia Fizyczna, 2018)
In the early 19th century, cartographic studies typically satisfied military or administrative needs. The idea behind drawing a map of Pleszew in 1806 was to show the condition of the city following a great fire. The plan distinguishes between the burnt down areas and ones saved from the fire. While the legend is small, including few explanations and the markings on the sheet are moderately distributed, the analyzed city map is a valuable resource of information which can be presented in the form of thematic visualizations. The article presents studies into the information provided by the map of Pleszew in terms of the scope of content and its spatial distribution; a method of arrangement thereof has also been proposed. The decision to attribute specific objects to separate layers has offered an opportunity of selecting the content according to various criteria and presenting it in the form of thematic visualizations.